Monosaccharides quantified in sediment cores from coastal vegetated ecosystems - Inga Hellige; Aman Akeerath Mundanatt; Theresa-Marie Fett; Mirco Wölfelschneider; Jennifer Prugger; Jana K Geuer; Svenja Reents (PANGAEA, 2025)
50-cm deep sediment cores were taken in saltmarsh, seagrass, mangroves and unvegetated areas around the German Bight, Malaysia and Columbia in 2022 and 2023. Up to 3 points per ecosystem were sampled along a transect, in total 93 cores were analysed. Carbohydrates were sequentially extracted using MilliQ-water and 0.3 M EDTA for later analyses. Extracts were acid hydrolysed (1 M HCl, 24 h, 100°C) and monosaccharides were analysed using anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD), according to Engel et al., 2011. Briefly, sample analysis was performed using a Dionex ICS-5000+ system with a CarboPac PA10 analytical column (2 exttimes 250 mm) and a CarboPac PA10 guard column (2 exttimes 50 mm). Neutral and amino sugars were separated under isocratic conditions with 18 mM NaOH, while acidic monosaccharides were separated using a gradient up to 200 mM NaCH?COO.